1980
DOI: 10.1007/bf00255268
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of bratton-marshall-positive material in mice following intravenous injections of nitrosoureas

Abstract: As determined by a colorimetric assay measuring parent compounds plus ether-extractable nitroso-containing metabolites, N,N'-bis(2-chloroethyl)-N-nitrosourea (BCNU) disappeared more rapidly than N-(2-chloroethyl)-N'cyclohexyl-N-nitrosourea (CCNU) and N-(2-chloroethyl)-N'-(4-transmethylcyclohexyl)-N-nitrosourea (MeCCNU) and their products from the tissues of mice injected IV. Assay of selected samples by high-pressure liquid chromatography revealed that the colorimetric assay for BCNU was specific in that the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Not only does carmustine have a high lipid solubility, but it also has been shown to readily cross the blood–brain barrier, leading it to become one of the most clinically used drugs for brain tumor treatment . However, it is not popularly used for other malignant tumors due to its lack of target specificity and easy cell membrane fusion in normal tissues during regular body circulation . By varying the volume ratio of oleosome, we found that 1:50 (oleosome/PBS) or less ratio of oleosome solution had a negligible effect on survivability under the daily intravenous injection condition, whereas over 1:10 ratio of oleosome solution was found to be toxic after 1 h injection by the obstruction of blood flow.…”
Section: Resultsmentioning
confidence: 91%
“…Not only does carmustine have a high lipid solubility, but it also has been shown to readily cross the blood–brain barrier, leading it to become one of the most clinically used drugs for brain tumor treatment . However, it is not popularly used for other malignant tumors due to its lack of target specificity and easy cell membrane fusion in normal tissues during regular body circulation . By varying the volume ratio of oleosome, we found that 1:50 (oleosome/PBS) or less ratio of oleosome solution had a negligible effect on survivability under the daily intravenous injection condition, whereas over 1:10 ratio of oleosome solution was found to be toxic after 1 h injection by the obstruction of blood flow.…”
Section: Resultsmentioning
confidence: 91%
“…High-pressure liquid chromatography (HPLC) and a colorimetric assay using the Bratton-Marshall reagent can both be used to quantify BCNU (2,(26)(27)(28) . The Bratton-Marshall method was preferred for this study to quantify the intact BCNU molecule due to ability to process larger numbers of samples in parallel.…”
Section: Discussionmentioning
confidence: 99%
“…A simple and inexpensive colorimetric BCNU assay [8][9], based upon the sulfanilamide assay developed by Bratton and Marshall [10] was utilized. A major advantage of this assay derivatization was that only the intact BCNU molecule was quantitated.…”
Section: Bratton-marshall Colorimetric Assaymentioning
confidence: 99%